Atypical Features of Chikungunya Infection - Dutta, Pradip Kumar; Dutta, Arup; Rashid, Md Mamunur; Dutta, Sudipa (Journal of Chittagong Medical College Teachers’ Association, 2017)
Typical chikungunya virus (CHIKV) infection results in an acute febrile illness characterized by fever, severe joint pain and rash. Although chikungunya is generally not considered life threatening, atypical clinical manifestations resulting in significant morbidity have been documented, especially during epidemics. Our review is intended to elicit clinicians awareness of the atypical and severe forms of the disease in our region, as a way to potentially improve the outcomes of such life-threatening conditions. JCMCTA 2017 ; 28 (1) : 3 - 7